Macan Ali In The Cirebon Glass Painting: The Study Of Ethnomathematics - Tegar Perkasa Wahyusukma; Arif Muchyidin; Indah Nursuprianah (MASI Mandiri Edukasi, 2022)
The research objectives are: 1) Knowing the history and development of the Macan Ali and the typical Cirebon glass painting. 2) Knowing the mathematical elements in the typical Cirebon Ali Macan glass painting. The research method used by the researcher is descriptive qualitative research with interview data collection techniques, observations, documentation and field notes. The research results are the history of the Macan Ali, which means the association of the Cirebon indigenous people who are great linuhung or holding fast to the belief of an almighty god. The mathematical element found in the Macan Ali is the golden ratio worth 1.618... . The Golden Ratio used by the researcher is the Golden Rectangle and the Golden Ellipse. First, there are 3 Golden Rectangles on the two macan eyes, the front and back legs of the Macan Ali and the formation of the tail pattern and the overall Macan Ali's difference of 0.155 and 0.164. Then, 1 Golden Ellipse is found in the shape of the Ali Macan body. Meanwhile, in typical Cirebon glass paintings, there are elements of transformation (Reflection, Translation, Dilation, and Rotation), namely, reflection or reflection on the making of the Macan Ali pattern in glass media, translation and rotation on the mega cloudy carving, and dilatation on the wadasan carving. From this research, it is hoped that this will provide readers with insight and knowledge regarding the typical Cirebon Macan Ali glass painting and the mathematical elements contained in it and can preserve the art, culture, and history through the typical Cirebon Macan Ali glass painting